'Lest we forget'*: a veteran and son share a 'warfare tourism' experience. Issue 1 (1st January 2017) - Fallon, Paul; Robinson, Peter
ABSTRACT: 'Warfare tourism' represents an increasingly significant dimension of contemporary tourism. This paper provides a fresh perspective on participation in 'warfare tourism' by investigating the behaviour and experiences of a living veteran and his son returning to two theatres of war in which the veteran had served in the Royal Navy during the Second World War. Active interviews with the two family members were used to gather rich data regarding the two extended trips, which had been funded by 'Heroes Return', to Australia in 2012 and Sri Lanka in 2013. The findings indicate that some of the facets of visiting the fallen at other dark tourism sites, such as empathetic identification and personal connection, are also very relevant to trips shared between the living. However, with the living these contribute to a powerful co-created experience in which 'closer' bonds between the travellers can be developed. Furthermore, whilst the experiences at times represented 'bitter-sweet' nostalgia for the veteran, they also provided the son with the opportunity to 'look through his father's eyes' from both a past and current perspective. Given that there will be war veterans as long as conflicts exist, the results have valuable messages for all those dealing with veterans in the future.